Self-directed Learning: Strategy to Increase Digital Literacy in Suburban Society - Nugroho, Rivo; Roesminingsih, MV.; Lestari , Gunarti Dwi; Rosyanafi , Rofik Jalal; Yulianti, Endah (Mimbar Ilmu, 2024)
The impact of digital technology in urban areas has a big influence on suburban communities, from mindset to use of technology. The development of digital technology has caused new upheavals in suburban society; the VUCA era has become a new chapter. Therefore, it is necessary to be equipped with digital literacy. This research aims to describe and analyze research findings regarding the impact of self-directed learning on digital literacy in suburban society. This research uses a qualitative approach with a grounded theory method. Research was conducted on suburban societies, youth organizations, community facilitators, and stakeholders through participatory observation techniques, in-depth interviews, and document studies. Data analysis uses open, axial, and selective coding data analysis. The research results show that the process of self-directed digital literacy learning in suburban communities is manifested in the community's proactive attitude with the presence of digital technology and social media. The construction of knowledge and learning experiences in building digital literacy in suburban communities is realized in the community's appreciation for the presence of digital technology, which is interpreted as providing convenience, new insights, and benefits. Apart from that, it is an informal learning medium, a mass communication tool, a discussion forum, a medium for social interaction in cyberspace, and an exploration of skills and knowledge in social media. This research concludes that self-directed learning is a strategy for suburban society to improve digital literacy skills.